The Impact of the 2008 Global Financial Crisis on the Health of Canadians - Omar, Sabrina (Université d'Ottawa / University of Ottawa, 2015)
Despite a clear impact on the Canadian economy, little is known about the subsequent health impacts of the 2008 Global Financial Crisis (GFC). This thesis aims to fill this gap in knowledge by conducting a secondary analysis of Canadian Community Health Survey (CCHS) data to assess the impact of the GFC on health in Canada – a country that has not yet been thoroughly studied from this angle. Based on when the respondent completed the survey, exposure to the GFC was categorized into four phases: pre-crisis, crisis, stimulus, and austerity. Outcomes investigated include measures of mental health, physical health, and health-related behaviours. Statistically significant associations were observed between several health outcomes and the austerity period as compared to the pre-crisis period. Austerity has been linked to worsening health in other studies and represents an example of how the policy response can have greater detrimental impact on health than the financial crisis itself.
Keywords: Austerity; Financial Crisis; Mental Health; CCHS; Recession; Risky health behaviours; Canada